Mosaic‐activating FGFR2 mutation in two fetuses with papillomatous pedunculated sebaceous naevus. (2nd October 2016) - Kuentz, P.; Fraitag, S.; Gonzales, M.; Dhombres, F.; St‐Onge, J.; Duffourd, Y.; Joyé, N.; Jouannic, J.‐M.; Picard, A.; Marle, N.; Thevenon, J.; Thauvin‐Robinet, C.; et al.
Summary: Papillomatous pedunculated sebaceous naevus (PPSN) has been described as a subtype of sebaceous naevus (SN), typically affecting the scalp and face. In contrast with Schimmelpenning syndrome, no cerebral, ocular or skeletal anomalies have hitherto been reported. We report two unrelated fetuses with PPSN, one with large pink exophytic tumours, the other with minor features but similar microscopic findings. We performed whole‐exome sequencing in affected skin tissue from fetus 1, which identified a postzygotic de novo FGFR2 c.1144T>C (p.Cys382Arg) mutation in 34·6% of reads which was absent in the parents' blood. Targeted deep sequencing of FGFR2 confirmed its mosaic status in additional affected skin from fetus 1, and identified the same substitution in 26% of reads in affected skin from fetus 2. FGFR2 p.Cys382Arg is a known somatic driver mutation in human cancer, previously reported to result in activation of RAS signalling. A similar paralogous missense mutation in the transmembrane domain of FGFR3 (p.Gly380Arg) has been reported in keratinocytic epidermal naevi. Our findings define a distinct clinical and molecular subgroup of SN, beside HRAS or KRAS ‐related SN, and expand the spectrum of mosaic skin conditions associated with receptor tyrosine kinase mutations. Abstract : What's already known about this topic? A rare subtype of papillomatous pedunculated sebaceous naevus (PPSN) has been reported in neonates and a fetus. Most epidermal naevi have been associated with postzygotic mutations in genes encoding cell growth and proliferation signalling molecules: HRAS and KRAS in sebaceous naevi (SN), FGFR2 in acne or comedo naevi, and HRAS, KRAS, NRAS, FGFR3 and PIK3CA in keratinocytic epidermal naevi. What does this study add? Here we report a novel postzygotic activating FGFR2 mutation in two unrelated fetuses with PPSN. Mosaic receptor tyrosine kinase gene mutations, particularly in FGFR2, have not previously been reported in SN. Linked Comment: Has. Br J Dermatol 2017; 176 :15–16 .